# Function tables with two-step rules Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to Function tables with two-step rules. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using Show Answer button. You can use Next Quiz button to check new set of questions in the quiz.

Q 1 - Fill in the table using this function rule.

y = 3x + 1

### Explanation

Step 1:

In y = 3x + 1, for x = 0, y = 1; for x = 1, y = 3(1) + 1 = 4; Similarly, for x = 2, y = 7; for x = 3, y = 10 and for x = 4, y =13.

Step 2:

Making a table of x and y values we get

Q 2 Fill in the table using this function rule.

y = 2x − 3

### Explanation

Step 1:

In y = 2x − 3, for x = 0, y = −3; for x = 1, y = 2(1) − 3 = − 1; Similarly, for x = 2, y = 1; for x = 3, y = 3 and for x = 4, y = 5.

Step 2:

Making a table of x and y values we get

Q 3 Fill in the table using this function rule.

y = 5x − 3

### Explanation

Step 1:

In y = 5x − 3, for x = 0, y = −3; for x = 1, y = 5(1) − 3 = 2; Similarly, for x = 2, y = 7; for x = 3, y = 12 and for x = 4, y = 17.

Step 2:

Making a table of x and y values we get

Q 4 Fill in the table using this function rule.

y = 3x − 5

### Explanation

Step 1:

In y = 3x − 5, for x = 0, y = −5; for x = 1, y = 3(1) − 5 = −2; Similarly, for x = 2, y = 1; for x = 3, y = 4 and for x = 4, y = 7.

Step 2:

Making a table of x and y values we get

Q 5 Fill in the table using this function rule.

y = 2x + 2

### Explanation

Step 1:

In y = 2x + 2, for x = 0, y = 2; for x = 1, y = 2(1) + 2 = 4; Similarly, for x = 2, y = 6; for x = 3, y = 8 and for x = 4, y = 10.

Step 2:

Making a table of x and y values we get

Q 6 Fill in the table using this function rule.

y = 5x + 1

### Explanation

Step 1:

In y = 5x + 1, for x = 0, y = 1; for x = 1, y = 5(1) + 1 = 6; Similarly, for x = 2, y = 11; for x = 3, y = 16 and for x = 4, y = 21.

Step 2:

Making a table of x and y values we get

Q 7 Fill in the table using this function rule.

y = 3x − 3

### Explanation

Step 1:

In y = 3x − 3, for x = 0, y = −3; for x = 1, y = 3(1) − 3 = 0; Similarly, for x = 2, y = 3; for x = 3, y = 6 and for x = 4, y = 9.

Step 2:

Making a table of x and y values we get

Q 8 Fill in the table using this function rule.

y = 4x + 2

### Explanation

Step 1:

In y = 4x + 2, for x = 0, y = 2; for x = 1, y = 4(1) + 2 = 6; Similarly, for x = 2, y = 10; for x = 3, y = 14 and for x = 4, y = 18.

Step 2:

Making a table of x and y values we get

Q 9 Fill in the table using this function rule.

y = 2x − 2

### Explanation

Step 1:

In y = 2x − 2, for x = 0, y = − 2; for x = 1, y = 2(1) − 2 = 0; Similarly, for x = 2, y = 2; for x = 3, y = 4 and for x = 4, y = 6.

Step 2:

Making a table of x and y values we get

Q 10 Fill in the table using this function rule.

y = 5x − 2

### Explanation

Step 1:

In y = 5x − 2, for x = 0, y = − 2; for x = 1, y = 5(1) − 2 = 3; Similarly, for x = 2, y = 8; for x = 3, y = 13 and for x = 4, y = 18.

Step 2:

Making a table of x and y values we get

function_tables_with_two_step_rules.htm